Chronic Care Model Based Nursing Interventions Improve Hypertension Patient’s Medication Compliance by Preventing Patients Forget and Fear - Jujuk Proboningsih; Sriyono Sriyono; Mohammad Najib; Fitriah Fitriah (International Journal of Advanced Health Science and Technology, 2023)
The goal of nursing intervention on chronic disease such as Hypertension is to improve the patient self-care, in which the Chronic care model could help to reach the best outcome. Research suggests the community, health workers, and regulations could improve the health. The purpose of this study was to apply nursing intervention based on chronic care model to medication adherence in hypertensive patients. This is quasi-experimental research used pre-post test control group design. 50 respondents of hypertension patients were recruited from Pucang Sewu, Pacar Keling and Tambak Rejo Surabaya Health Centres. The intervention was applicating nursing interventions based on the Chronic Care Model. The Mann Whitney U statistical analysis used to understand the effect of the intervention to the medication adherence in patients with hypertension. A total of 50 respondents who were divided into two groups, control and treatment, with each (n = 25). The distribution of characteristics in the two groups is homogeneous. Different test in the control group, there was no difference. The treatment group shown a significant difference in adherence before and after the intervention with p value 0.000 (p <0.05). This study found the reason of disobedient patient to medication, which is forget and fear to the side effect. The patient and the health care agree frequent reminder could be the solution to this problem. Chronic Care Model based nursing interventions can improve medication adherence in hypertensive patients by encourage the health care system to frequently remind patients.